The Themes Have to Be Considered in the Change Process Within Healthcare Organizations: Critical Analysis Review - Alsaqqa HH (Journal of Multidisciplinary Healthcare, 2025)
Hatem H Alsaqqa1,2 1Al-Quds University, Deanship of Scientific Research, Al-Quds University, Jerusalem, Palestine; 2Palestinian Ministry of Health, Gaza, PalestineCorrespondence: Hatem H Alsaqqa, Email hs-mch@hotmail.comAbstract: This review is intended to scrutinize different articles’ types and determine a suitable process, model or framework for successful change in healthcare organizations. An integrative review of the literature was conducted. The search strategy began with three electronic databases (EBSCOhost, Google Scholar and PubMed). Considering the inclusion criteria, published articles that examined the change process within the healthcare organizations in the timeframe between 2000 and 2023 were chosen. Results extraction and analysis were completed on all the included articles. The final sample for this review comprised 19 studies. Based on common meanings and vital issues, 8 main themes contributing to change in healthcare organizations were integrated and grouped into four main categories (process dimensions), two adjunct factors (strategic dimensions) and one mediating tool and a result category. The four main categories are readiness to change, team-building, tangible and intangible variables’ characteristics and the two adjunct factors are the metaphor design and time perspective. In addition to technology as a mediating role for change and the scale of the change as a resulted outcome. In general, collections that emerged in this study could be useful for framing initiatives to arouse organizational change in healthcare. However, little is known about the relative significance of each acknowledged factor within the change process in healthcare organizations. Various methodological research is recommended for narrowing this gap. Before beginning the change process, ongoing studies should focus on the psychological features of organizational scales for healthcare contexts.Keywords: change, healthcare, critical analysis review, organization, theme